2017
DOI: 10.5713/ajas.16.0677
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of late-incubation egg amniotic fluid and a potential in ovo feed supplement

Abstract: ObjectiveThis study explored the physico-chemical properties of late-incubation egg amniotic fluid and a potential in ovo feed (IOF) supplement.MethodsAmniotic fluid was collected from broiler breeders (Ross 308, 51 weeks and Cobb 500, 35 weeks) on day 17 after incubation. A mixture of high-quality soy protein supplement – Hamlet Protein AviStart (HPA) was serially diluted in MilliQ water to obtain solutions ranging from 150 to 9.375 mg/mL. The mixtures were heat-treated (0, 30, 60 minutes) in a waterbath (80°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The amnion encloses the embryo during development; the inner cell layer secretes amniotic fluid, which protects the embryo from mechanical and thermal shocks and prevents dehydration. Shortly before hatching (ED17), the embryo ingests amniotic fluid as a source of water and nutrients ( De Oliveira, 2007 ; Omede et al., 2017 ). Amniotic fluid intake is also crucial for intestinal mucosa development and preparation for hatching because the ability to digest and absorb nutrients is poorly developed at this stage ( De Oliveira, 2007 ).…”
Section: Metabolic Changes In Chicken Embryosmentioning
confidence: 99%
See 1 more Smart Citation
“…The amnion encloses the embryo during development; the inner cell layer secretes amniotic fluid, which protects the embryo from mechanical and thermal shocks and prevents dehydration. Shortly before hatching (ED17), the embryo ingests amniotic fluid as a source of water and nutrients ( De Oliveira, 2007 ; Omede et al., 2017 ). Amniotic fluid intake is also crucial for intestinal mucosa development and preparation for hatching because the ability to digest and absorb nutrients is poorly developed at this stage ( De Oliveira, 2007 ).…”
Section: Metabolic Changes In Chicken Embryosmentioning
confidence: 99%
“…In the final third of incubation, the internal environment changes considerably, leading to significant shifts in embryonic metabolism. The ingestion of amniotic fluid initiates at approximately 17 d of ED ( ED17 ) ( Uni and Ferket, 2003 ; Lu et al., 2007 ; De Oliveira et al., 2008 ; Omede et al., 2017 ) and substrates become available to be deposited in glycogen stores ( Uni and Ferket, 2003 ). Oxygen availability decreases with the rupture of the chorioallantoic membrane on ED19, and the use of fatty acids becomes ineffective and unable to meet the embryonic energy demands ( Moran, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…We base this hypothesis on previous ndings in pigs, which showed that leucine supplementation was most effective in enhancing epithelial cell proliferation when combined with isoleucine and valine (47). Furthermore, amino acid pro ling of the amniotic uid of E17 chick embryos revealed that leucine content was higher than isoleucine and valine (48). These data indicate that amniotic administration of an additional 6 mg of leucine by IOF may have disrupted BCAA ratios, resulting in a reduced induction of SI epithelial proliferation, compared to the potential effects of IOF of leucine combined with other BCAAs.…”
Section: Discussionmentioning
confidence: 79%
“…About the endogenous VC absorption during embryonic development, the part is from the mixture of amniotic fluid and albumen [21,22], the other is absorbed from yolk sac [17,23]. Dynamic changes of SVCT1 expression matched the behavior of embryo swallowing amniotic fluid and yolk sac internalization into abdominal cavity [8,16].…”
Section: Discussionmentioning
confidence: 99%